2020
DOI: 10.1108/gm-11-2019-0201
|View full text |Cite
|
Sign up to set email alerts
|

Women in STEM/SET: gender gap research review of the United Arab Emirates (UAE) – a meta-analysis

Abstract: Purpose The purpose of this paper is to conduct a meta-analysis of existing research on gender discrimination/gender gap and women in Science, Technology, Engineering and Mathematics (STEM) in the UAE, specifically, and Middle East and North Africa (MENA) and Gulf Cooperation Council (GCC) countries in general because of very limited number of articles published on the subject. It will give future researchers insights into the topics, methodologies and findings of such research from 1999–2019. Design/methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 65 publications
0
22
0
Order By: Relevance
“…Previous studies have shown there is much to be gained by policies (Metcalfe, 2008). For example, in the UAE, Patterson et al (2020) show that gender discrimination is on the decline, yet the problem still exists, necessitating efforts from policy makers, society, and governments to attain gender parity. Several efforts have been made by the Gulf Cooperation Council (GCC) states, particularly the United Arab Emirates and Saudi Arabia, which have significantly expanded their promotion of women in public life in recent years, with more women achieving high positions in a variety of social areas (Abdulkadir & Müller, 2020;Parveen, 2021;Rizvi & Hussain, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown there is much to be gained by policies (Metcalfe, 2008). For example, in the UAE, Patterson et al (2020) show that gender discrimination is on the decline, yet the problem still exists, necessitating efforts from policy makers, society, and governments to attain gender parity. Several efforts have been made by the Gulf Cooperation Council (GCC) states, particularly the United Arab Emirates and Saudi Arabia, which have significantly expanded their promotion of women in public life in recent years, with more women achieving high positions in a variety of social areas (Abdulkadir & Müller, 2020;Parveen, 2021;Rizvi & Hussain, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Gender coupled with religion meant deference to family decisions which could be capricious; also, they were segregated on campus although most wished not to be. Employment opportunities could be equally unpredictable as several commentators noticed (Engin & McKeown, 2016;Patterson et al, 2020). Prior school education and English as the medium of instruction meant that many had to make considerable adaptations to meet the demands of successful university study.…”
Section: Discussionmentioning
confidence: 99%
“…(p. 13). The evidence for this remains ambivalent (Patterson et al, 2020). Engin and McKeown (2016) studied aspects of motivation of Emirati university students, both male and female.…”
Section: Emirati Women In Higher Education In the Uaementioning
confidence: 99%
See 2 more Smart Citations